ANALISIS PENGARUH PERKEMBANGAN PENANAMAN MODAL DALAM NEGERI (PMDN) DAN PENANAMAN MODAL ASING (PMA) TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TENGAH (PERIODE 1985-2014) - Aprilia DwiRatna Sari; Dody - Setyadi; Umar - Farouk (Politeknik Negeri Semarang, 2015)
This study aims to determine the influence ofthe growth of Domestic Investment (DCI) andForeign Direct Investment (FDI) onemployment in Central Java. Research onemployment was conducted in Central Javafor the period of 1985 to 2014 by usingmultiple linear regression analysis. Theresults of this study indicate that employmentin Central Java is effected by variableDomestic Invesment and Foreign DirectInvestment by 51,1%. This study finds asignificant positive relationship between thevariable of Domestic Investment (DCI) onemployment in the Central Java, whileForeign Direct Investment (FDI) has asignificant but negative effect on employmentin Central Java. Based on this research, theauthor provides advice for DCI and FDI toincrease employment in Central Java -Indonesia.